(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Already, artificial intelligence (AI) is all around us, from self-driving cars and drones to virtual assistants and software that translate or invest. Impressive progress has been made in AI in recent years, driven by exponential increases in computing power and by the availability of vast amounts of data, from software used to discover new drugs to algorithms used to predict our cultural interests. Digital fabrication technologies, meanwhile, are interacting with the biological world on a daily basis. Engineers, designers, and architects are combining computational design, additive manufacturing, materials engineering, and synthetic biology to pioneer a symbiosis between microorganisms, our bodies, the products we consume, and even the buildings we inhabit. Companies in the technology, media, and telecommunications industry expect AI to have a significant impact on product offerings in the next five years. This research contains the data from a pilot survey from Latvian business executives’ expectations for AI and robotics for the next 5 years. The aim of this research is to find out if AI and robotics will make significant impact on workplaces in Latvia in the next five years.